1998
DOI: 10.1046/j.1365-2249.1998.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of anti-PL-12 autoantibodies by ELISA using a recombinant antigen; study of the immunoreactive region

Abstract: SUMMARYAutoantibodies to aminoacyl-tRNA synthetases are highly associated with myositis and detection is important in clinical diagnosis; however, current methods of screening limit its clinical utility. In the present study, alanyl-tRNA synthetase (PL-12) recombinant protein was obtained by immunological screening of a HeLa expression library and used in an ELISA with 22 anti-PL-12 sera, 200 autoimmune sera negative for PL-12 and 100 healthy individual sera. Sensitivity of the method was 95% (21/22) and speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…On the other hand, in 2021 there was an increase in anti-PL-7 and anti-PL-12 autoantibodies, suggesting that SARS-CoV-2 vaccination might induce a strong reactions between Spike 1 proteins and a variety of tissue antigens in genetically predisposed individuals. It has been postulated that the presence of IIM antibodies in sera from patients suffering from myositis reflects a previous specific viral infection, based on previously reported interaction between some synthetases and the RNA of certain picornaviruses [ 18 , 19 ]. A study in dermatomyositis patients identified three T cell receptor epitopes specific to SARS-CoV-2 suggesting a potential for the virus to contribute to myositis development [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in 2021 there was an increase in anti-PL-7 and anti-PL-12 autoantibodies, suggesting that SARS-CoV-2 vaccination might induce a strong reactions between Spike 1 proteins and a variety of tissue antigens in genetically predisposed individuals. It has been postulated that the presence of IIM antibodies in sera from patients suffering from myositis reflects a previous specific viral infection, based on previously reported interaction between some synthetases and the RNA of certain picornaviruses [ 18 , 19 ]. A study in dermatomyositis patients identified three T cell receptor epitopes specific to SARS-CoV-2 suggesting a potential for the virus to contribute to myositis development [ 20 ].…”
Section: Discussionmentioning
confidence: 99%